Analisis Pengaruh Kenaikan Tarif Pajak Pertambahan Nilai Terhadap Volume Penjualan Pada CV. Harko Jaya Offset - Rosyta Devi Arifianti Putri; Khasanah Sahara; Imarotus Suaidah (Journal Economic Excellence Ibnu Sina, 2023)
This research is motivated by a government policy in 2021 to increase the Value Added Tax (VAT) rate by 11% starting on April 1 2022. In this policy, CV. Harko Jaya Offset is a business actor in the printing and trading sector of paper and plastic. As a Party subject to VAT when selling and purchasing goods. This research aims to determine the effect of increasing the Value Added Tax (VAT) rate on sales. The analysis technique used is quantitative descriptive analysis with analytical tools, calculating Value Added Tax (VAT) rates of 10% and 11%, calculating the amount of tax paid, calculating sales volume and calculating the increase/decrease in sales volume. The results of this research show that there is no influence on product sales from the increase in the Value Added Tax rate, because the company still uses the same selling price. It can be proven from the calculation results that sales volume increased by 58.19%. The results of this analysis are different from research from (Putri, 2022), (Djufri, 2022) and (Wibowo, 2021) which show that an increase in the Value Added Tax rate has an effect on declining sales. Suggestions on CV. Harko Jaya continues to use the same selling price for all products in each sale to maintain sales volume in the event of an increase in the VAT rate. And it is hoped that future researchers will be able to develop their research, one of which is on selling prices after VAT.